Application of Nano-Titanium Dioxide in Food Antibacterial Packaging Materials - Jiarui Li; Dequan Zhang; Chengli Hou (Bioengineering)
Food waste and food safety issues caused by food spoilage have been brought into focus. The inhibition of food spoilage bacteria growth is the key to maintaining food quality and extending the shelf life of food. Photodynamic inactivation (PDI) is an efficient antibacterial strategy which provides a new idea for the antibacterial preservation of food. Nano-titanium dioxide (nano-TiO2) with PDI characteristics has attracted the interest of many researchers with its elevated efficiency, broad-spectrum antibacterial resistance, low cost, safety, and non-toxicity. Nano-TiO2 photodynamic antibacterial properties have been studied extensively and has a great application value in the field of food packaging. The antibacterial properties of nano-TiO2 are linked to its photocatalytic activity and are influenced by factors such as reactive oxygen species production, bacterial types, etc. Polymer-based nano-TiO2 packaging has been prepared using various methods and applied in various foods successfully. In this review, the latest research on photocatalytic and antibacterial mechanisms and factors of nano-TiO2 is discussed, and its applications in food antibacterial packaging are also explored comprehensively. Challenges and future perspectives for nano-TiO2-based food packaging applications have been proposed. This review aims to provide a whole comprehensive understanding of novel antibacterial packaging systems based on nano-TiO2.